2002
DOI: 10.1197/aemj.9.9.896
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Cardiac Events in Emergency Department Patients with Chest Pain Six Months after a Negative Inpatient Evaluation for Acute Coronary Syndrome

Abstract: Objective: To evaluate the impact of the diagnostic test setting-inpatient versus outpatient-on adverse cardiac events (ACEs) after six months in emergency department (ED) patients with chest pain who were admitted to the hospital and subsequently had a negative evaluation for acute coronary syndrome (ACS). Methods: The authors retrospectively studied a consecutive sample of ED patients with chest pain over a nine-month period. All patients were admitted to the hospital and underwent negative evaluations for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Perhaps surprisingly, the women also had a higher death rate, but from non-cardiac causes. Of interest is the fact that her outcomes were in keeping with those previously reported [8], even where patients had a negative in-patient workup for chest pain [9], but worse.…”
supporting
confidence: 59%
“…Perhaps surprisingly, the women also had a higher death rate, but from non-cardiac causes. Of interest is the fact that her outcomes were in keeping with those previously reported [8], even where patients had a negative in-patient workup for chest pain [9], but worse.…”
supporting
confidence: 59%
“…We assessed study quality numerically (1)(2)(3)(4)(5), using a modified Jadad scale for treatment studies (7 ) ( Table 1). This proposed quality score is a nonstandardized score defined for the purposes of this study because no validated quality score exists for the review of diagnostic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Manini et al evaluated the impact of the diagnostic test setting (inpatient vs. outpatient) on adverse cardiac events at 6 months in patients who were admitted to the hospital and had negative initial evaluations for acute coronary syndrome. They concluded that the risk of adverse cardiac events was significantly higher in patients scheduled for outpatient diagnostic testing (13).…”
mentioning
confidence: 99%